Information Economy Report 2009 - United Nations Conference on Trade; Development (United Nations, 2009)
The Information Economy Report 2009: Trends and Outlook in Turbulent Times (IER 2009) is the fourth in a series published by the United Nations Conference on Trade and Development (UNCTAD). The report is one of the few publications to monitor global trends in information and communication technologies (ICTs) as they affect developing countries. It serves as a valuable reference for policymakers in those nations. It gives special attention to the impact of the global financial crisis on ICTs. The report offers a fresh assessment of the diffusion of key ICT applications between 2003 and 2008. It includes chapters on the use of ICTs in the business sector and on the impact of the financial crisis on ICT trade.